Effect of ovarian autotransplantation on FSH levels in Wistar rats late menopause model - Abdurahman Laqif; Dewi Kartika DJ Anwar; Eriana Melinawati (Majalah Obstetri dan Ginekologi, 2018)
Objectives: To determine the effect of ovarian autotransplan-tation on decreasing FSH level in Wistarrats late menopause model.Materials and Methods: Experimental analytic research on 27 Wistar rats (Rattus novergicus) was divided into 3 groups. Group 1 (K1) or control. Group 2 (K2) performed bilateral oophorec-tomy without autotransplantation. Group 3 (K3) performed bilateral oophorectomy with autotransplantation. Measurements of FSH levels were performed on the first day, day 28 (four weeks after bilateral oophorectomy, during late menopause) and 56 day (four weeks after autotransplant). Measurement of FSH levels using ELISA. Data analysis used ANOVA and Post Hoc test.Results: The mean FSH level measured on day 56 at K1 = 63.400 ng/mL, at K2 = 78.416 ng/mL and K3 = 31.991 ng/mL. There were significant differences between K1 and K2 (p = 0,000), K1 and K3 (p = 0,000), and between K2 and K3 (p = 0,000).Conclusion: Ovarian autotransplantation decrease FSH levels in Wistar rats late menopause model.